Computational multi-scale analysis of simultaneous processes of delamination and damage accumulation in laminated composites - Mikhail Tashkinov; Daria Ershova; Aleksandr Shalimov (Fracture and Structural Integrity)
When studying mechanical behavior of structures made of laminated polymer composite materials, issues related to their relatively high susceptibility to damage, such as delamination, fiber breakage and matrix failure, play significant role. Key aspects are also related to accurate description of the internal structures and heterogeneity of the material. This work is aimed at a numerical study of the processes of damage accumulation in plies as well as development of delamination in laminated polymer composite L-shaped specimen taking into account microstructural parameters. The influence of contact conditions between the plies on the models behavior has been studied. It was established that the delamination processes inside the specimen can initiate at the early stages of deformation, which is reflected in the difference of the results obtained using models with various numbers of separated plies. Comparison of the results of modelled elastic behavior of the specimen and models with the developed delamination leads to conclusions about influence of a number of model parameters on the results obtained before and after propagation of delamination. In particular, such factors as the geometry and mechanical properties of models, the number and conditions for specifying contact pairs in the model were analyzed.